Fifty modern thinkers on education : from Piaget to the present - Palmer, Joy, 1951-; Cooper, David E. (David Edward), 1942-; Bresler, Liora (London ; New York : Routledge, 2001)
Looks at fifty of the twentieth century's most significant contributors to the debate on education. Each essay gives key biographical information, an outline of the individual's principal achievements and activities, an assessment of his or her impact and influence and a list of their major writings and suggested further reading.
A.S. Neill, 1883-1973 / Peter Hobson -- Susan Isaacs, 1885-1948 / Robert Hinshelwood -- Harold Rugg, 1886-1960 / Stephen J. Thornton -- Ludwig Wittgenstein, 189-1951 / Nicholas C. Burbules and Michael Peters -- Martin Heidegger, 1889-1976 / Michael Bonnett -- Herbert Edward Read, 1893-1968 / Stephen Mark Dobbs -- Lev Semyonovich Vygotsky, 1896-1934 / Alexander Ardichvili -- Jean Piaget, 1896-1980 / Leslie Smith -- Michael Oakeshott, 1901-92 / Anthony O'Hear -- Carl Rogers, 1902-87 / Eleanor Feinberg and Walter Feinberg -- Ralph Winifred Tyler, 1902-94 / Elliot W. Eisner -- Burrhus Frederic Skinner, 1904-90 / Torsten Husén -- Harry Broudy, 1905-98 / Liora Bresler -- Simone Weil, 1909-43 / Richard Smith -- Joseph J. Schwab, 1910-88 / Ian Westbury and Margery D. Osborne -- Clark Kerr, 1911- / Debra D. Bragg and Frankie S. Laanan -- Benjamin S. Bloom, 1913-99 / Torsten Husén -- Jerome S. Bruner, 1915- / Howard Gardner -- Torsten Husén, 1916- / T. Neville Postlewaite -- Lee J. Cronbach, 1916- / Torsten Husén -- Donald Thomas Campbell, 1916-96 / Carol Taylor Fitz-Gibbon -- Maxine Greene, 1917- / Christine Thompson -- R.S. Peters, 1919- / John White -- John I. Goodlad, 1920- / Jianping Shen -- Paulo Freire, 1921- / Michael W. Apple, Luis Armando Gandin and Álvara Moreira Hypolito -- t Seymour B. Sarason, / Andrew Hargreaves -- Israel Scheffler, 1923- / Harvey Siegel -- Jean-François Lyotard, 1924-98 / Michalinos Zembylas -- Lawrence A. Cremin, 1925-90 / James D. Anderson -- Basil Bernstein F., 1925-2000 / Ivor F. Goodson -- Michel Foucault, 1926-84 / Michael Peters -- Margaret Donaldson, 1926- / Martin Hughes -- Ivan Illich, 1926- / David A. Gabbard and Dana L. Stuchul -- Lawrence Kohlberg, 1927-87 / K. Peter Kuchinke -- Paul H. Hirst, 1927- / Terence H. McLaughlin -- Philip Wesley Jackson, 1928- / Elliot W. Eisner -- Jane Roland Martin, 1929- / Susan Laird -- Nel Noddings, 1929- / David J. Flinders -- Jürgen Habermas, 1929- / Keith Morrison -- Carl Bereiter, 1930- / David R. Olson -- Pierre Bourdieu, 1930- / Ingólfur Ásgeir Jóhannesson and Thomas S. Popkewitz -- Neil Postman, 1931- / Dan Inbar -- Theodore R. Sizer, 1932- / Tamar Levin -- Elliot Eisner, 1933- / P. Bruce Uhrmacher -- John White, 1931- / Eamonn Callan -- Lee S. Shulman, 1938- / Pam Grossman and Sam Wineburg -- Michael W. Apple, 1942- / Carlos Antonio Torre -- Howard Gardner, 1943- / Mindy L. Kornhaber -- Henry Giroux, 1943- / Keith Morrison -- Linda Darling-Hammond, 1951- / Ann Lieberman.
Bibliografija uz tekst.
Keywords: filozofija odgoja i obrazovanja; povijest pedagogije; pedagozi - -- biografije